Kualitas Pelayanan Publik Pada Bidang Administrasi Kependudukan di Desa Mataindaha Kecamatan Pasi Kolaga Kabupaten Muna - Isnaini, Wilda; Ilato, Rosman; Igirisa, Irawaty (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe how the Quality of Public Service in the Population Administration Sector in Mataindaha Village, Pasi Kolaga District, Muna Regency, using several dimensions to measure the quality of service, namely: (1) Tangibles (physical evidence), (2) reliability, (3) responsiveness, (4) assurance, and (5) empathy. This study uses a qualitative descriptive method. With 10 (ten) research informants. Data collection techniques in this study consist of observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation (data display), and drawing conclusions. The results of this study reveal that the dimensions (1) tangibles are still lacking and need to be completed immediately. (2) assurance is also still lacking, which is indicated by village officials who have not been able to provide fast and timely services. While other dimensions such as (3) reliability. (4) responsiveness. (5) Empathy is good, where the apparatus is responsive in helping the community and is willing to re-explain service procedures that the community does not yet understand.